Optical and generation characteristics of new nonlinear Ba2Ga8GeS16 and Ba2Ga8(GeSe2)S14 crystals for the mid-IR range. (1st March 2022) - Badikov, V.V.; Badikov, D.V.; Shevyrdyaeva, G.S.; Laptev, V.B.; Melnikov, A.A.; Chekalin, S.V.
Abstract: Ba2 Ga8 GeS16 and Ba2 Ga8 (GeSe2 )S14 single crystals of large size and good optical quality have been grown for the first time. Their linear optical characteristics – transmission spectra in the range of 0.3 – 25 μm, dispersion of principal refractive indices, and birefringence – have been measured. Irradiation of the crystals by 100-fs laser pulses with a wavelength of 8.3 μm initiated second-harmonic generation with an efficiency comparable with that obtained for the AgGaS2 crystal.